2005
DOI: 10.1007/s11262-005-1797-7
|View full text |Cite
|
Sign up to set email alerts
|

Nucleic Acid Binding Property of the Gene Products of Rice stripe virus

Abstract: GST fusion proteins of the six gene products from RNAs 2,3 and 4 of the tenuivirus, Rice stripe virus (RSV), were used to study the nucleic acid binding activities in vitro. Three of the proteins, p3, pc3 and pc4, bound both single- and double-stranded cDNA of RSV RNA4 and also RNA3 transcribed from its cDNA clone, while p2, pc2-N (the N-terminal part of pc2) nor p4 bound the cDNA or RNA transcript. The binding activity of p3 is located in the carboxyl-terminus amino acid 154-194, which contains basic amino ac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
11
0

Year Published

2008
2008
2015
2015

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 31 publications
2
11
0
Order By: Relevance
“…This was consistent with the observation that Pc4 could only be detected in infected rice plants at a very early stage of infection [56,57]. In this scenario, the observed larger size of Pc4 when detecting with antisera to the protein in a previous report could be the result of polyubiquination [56,57].…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…This was consistent with the observation that Pc4 could only be detected in infected rice plants at a very early stage of infection [56,57]. In this scenario, the observed larger size of Pc4 when detecting with antisera to the protein in a previous report could be the result of polyubiquination [56,57].…”
Section: Discussionsupporting
confidence: 91%
“…It was suggested that the degradation might function to avoid extreme damage to the host and futile movement of the viral materials [52][53][54][55]. This was consistent with the observation that Pc4 could only be detected in infected rice plants at a very early stage of infection [56,57]. In this scenario, the observed larger size of Pc4 when detecting with antisera to the protein in a previous report could be the result of polyubiquination [56,57].…”
Section: Discussionsupporting
confidence: 77%
“…It has been reported that MPs encoded by tobamoviruses and dianthoviruses can bind single-stranded RNAs and transport them through PD in the form of ribonucleoprotein complexes (23,37,44). Liang et al (19) previously showed single-and double-stranded RNA-binding activities of RSV NSvc4 and suggested that the RNA-binding activities of NSvc4 may relate to a movement function. Our gel mobility shift assays, using purified NSvc4 protein and radioactively labeled RNA transcripts, also showed a sequence-nonspecific single-stranded RNA-and dsRNA-binding property for NSvc4.…”
Section: Discussionmentioning
confidence: 99%
“…The ribonucleoprotein particles (RNPs) represent the minimal infectious unit for RSV, which contains at least the RdRPs, CPs, and genome length viral RNAs (Ramírez and Haenni, 1994;Falk and Tsai, 1998). RSV NSvc4 interacts with the CP by using in vitro binding experiments (Zhang et al, 2008a) and binds nucleic acid (Liang et al, 2005a), suggesting that NSvc4 associates with the viral ribonucleocapsid for transport from cell to cell. These data suggest that the NS2 and NSvc4 of RSV may coordinate the formation of PD-associated structures that facilitate the intercellular movement of RSV in infected plants.…”
Section: Biological Functions Of Rsv-encoded Proteinmentioning
confidence: 99%